Teaching physicochemical quality parameters in oils for food engineering: implementation of practical laboratory work - Vargas-Neira, Samuel David; Rodríguez-Cepeda, Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article shows the results of a pilot didactic intervention, in which some contextualized Practical Laboratory Work (PLW) were designed and implemented, with the purpose of evaluating its impact on the significant learning of quality physicochemical parameters in edible oils. The intervention was carried out with a group of 14 food engineering students, where the students' responses to initial and final questionnaires, as well as practical work reports, were analyzed from a qualitative approach. It was identified that the design and implementation of PLW favors the significant learning of chemical concepts associated with the quality of oils in engineers in training. In this sense, the PLW promote criteria to evaluate the quality of a product in terms of acceptance or rejection, which allows the development of decision-making skills.